INSTRUMEN PENILAIAN KUALITAS TIDUR PADA ANAK - Khairun Nisa; Ika wahyuning Pertiwi; Alfonsius Ade Wirawan (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2023)
An enough sleep is necessary for physiological, emotional and mental development. The important of knowing and conducting an assessment to assess sleep quality and to find out the causes of sleep disorders so that they could provide the correct intervention according to the needs and problems experienced. The purpose of this literature review is to find out the types of questionnaires that could be used to measure the sleep quallity. The researched method used a literature studied approached with journals as sources, database search by using Scopus, Sciencedirect, and Pubmed. The Eligibility test for selected article used The Jonna Briggs Institute (JBI). The results of searched article, it was found that 5 articles that contained questionnaires that could be used to assess the sleep quality in children, they are the Children's Sleep Habits Questionnaire (CSHQ), Children's Sleep Assessment Questionnaire (CSAQ), Pittsburgh Sleep Quality Index (PSQI-T), Children's Sleep-Wake Scale (CSWS), Insomnia Severity Index (ISI), Athens Insomnia Scale (AIS), and Sleep Quality Index (SQI). It Found 8 types of questionnaires that could be used to assess sleep quality in children. This literature of study could be used to solve research problems that wanted to know more about the sleep problems in children.